Kinerja Keuangan UMKM Percetakan Digital: Peran Literasi Keuangan, Manajemen Keuangan, dan Inklusi Keuangan - Dwi Warni Wahyuningsih; Abdul Azis Arifai; Titi Rapini (Universitas Muhammadiyah Palembang, 2026)
This study examines the effect of financial literacy, financial management, and financial inclusion on the financial performance of digital printing MSMEs in Ponorogo Regency. Unlike previous studies that have largely focused on conventional MSME sectors, this research emphasizes the digital printing industry, which has received limited empirical attention despite its rapid growth and distinct financial characteristics. Using a quantitative approach, primary data were collected through questionnaires distributed to 30 active MSME owners selected using purposive sampling. The data were analyzed using multiple linear regression. The t-test results indicate that financial literacy and financial management do not significantly affect financial performance, suggesting that financial knowledge and administrative practices alone may not directly drive financial outcomes in this sector. In contrast, financial inclusion shows a positive and significant effect on financial performance, and the F-test confirms that all variables collectively have a significant influence. These findings provide new empirical evidence regarding the crucial role of financial inclusion in improving financial performance in the digital printing sector, thereby contributing to the development of MSME financial behavior theory and offering valuable insights for policymakers in designing strategies to enhance financial access and strengthen MSME sustainability.